Rocket: a Mediterranean crop for the world: Report of a workshop,13-14 December 1996, Legnaro (Padova), Italy - Padulosi, S.; Pignone, D.; International Plant Genetic Resources Institute (1997)
This publication represents the outcome of the second meeting of the Rocket Genetic Resources Network, an initiative launched in 1994 in the framework of IPGRI's project on Underutilized Mediterranean Species (UMS). The proceedings contain scientific contributions related to genetic resources, breeding and cultivation aspects of rocket, representing an extremely useful tool for all those interested in the cultivation and improvement of this crop. In particular, the paper on cultivation in the Veneto region can well be considered the first thorough scientific presentation ever made of rocket cultivation techniques in greenhouse environments. Apart from this paper, other contributions from India, Israel, Portugal and Turkey provide an overview of the degree of cultivation, uses and popularity of the crop around the world. Chapter III on International Cooperation provides a useful insight into the activity of the Rocket Network and supplies information on the initiatives promoted by UMS for safeguarding the genetic resources of this multipurpose crop.